The dark side of public visibility: How academic authors perceive and cope with anti-press hostility - Sibo Chen; Nicole Blanchett; S. Lecourt (Facts & Frictions)
As anti-press hostility intensifies globally, its impact on academics, whose presence as authors in journalism-based publications has increased in recent years, presents an understudied subject in communication and media studies literature. Approaching this subject using data from a survey of 732 authors affiliated with The Conversation Canada, a news startup specializing in explanatory journalism, this mixed-methods case study examined how academic authors perceive and cope with toxic comments and varying forms of anti-press hostility. Survey data are contextualized with qualitative interviews. The findings suggest that toxic comments pose a notable challenge to practice at The Conversation Canada. These comments are leading to self- censorship by causing a number of anti-press hostility, dark participation, digital trolling, harassment, hostility towards the press, online hate, toxic comments, The Conversation Canada, journalismthe affected authors to avoid expressing their viewpoints or writing about certain topics, as well as to reconsider their knowledge mobilization efforts. In sum, this study contributes to the body of literature on anti-press hostility and informs relevant public and policy discussions on the need to mitigate polarization online.